THE EFFECT OF PROJECT MANAGER COMPETENCE ON PROJECT SUCCESS IN CONSTRUCTION SERVICE CONTRACTOR COMPANIES - Saluri Saluri (Sean Institute, 2023)
Currently, building services have developed rapidly, especially in the field of infrastructure development. Because infrastructure needs will greatly benefit our country's economy. In these circumstances, a national construction service provider with substantial industrial expertise is required. The purpose of this study was to determine the effect of project manager competence on project success at PT. Nindya Karya (Persero). The research method uses descriptive and verification methods with a population of 20 PT managers. Nindya Karya (Persero). data analysis using simple linear regression analysis, these findings conclude that the competence of the project manager influences the success of the project at the construction service contractor company PT Nindya Karya (Persero).